Reformasi Birokrasi Terhadap Pelayanan Administrasi Terpadu Kecamatan (PATEN) Tahun 2014-2015 Studi Kasus Percepatan Izin UMK di Kecamatan Margadana Kabupaten Tegal - Pratiwi, Saras Adhisti Yulia; Harsasto, Priyatno (Journal of Politic and Government Studies, 2018)
The bureaucratic reformation of the Sub-district Integrated Administration Service for the acceleration of UMK licenses in Margadana sub-district of Tegal City aim for explaining the bureaucratic reformation which is implemented PATEN by Margadanana sub-district as one of the way to improving the quality of the services. The research determines the factors which influence the success of Implementation of PATEN. The research method uses Qualitative-descriptive method, where the information is collected from the staff of Margadana Sub-district Government, the Regional Secretariat of Tegal City, and some actors exclude the government institutions as data balancer. They are the citizens, and the policy observer in Tegal City.The results show the success of the Implementation of PATEN in Margadana Sub-district can be seen in implementation process through the behavior of the employees which handle the PATEN case, the infrastructures, the form of commitment for implementing PATEN, and the accountability of the services. They make Margadana Sub-district achieve the reward from theMinistry of cooperatives and Small Medium Enterprises Republic of Indonesia, and it becomes the pilot for the other sub-districts in Tegal City. The implementation of PATEN in Margadana Sub-district brings changes the performances of the employees of Government, and it impacts in the services for the community. The aim of PATEN is not only for improving the quality of the services in sub-district, but it has another aim to closer the services to the community. The changes happen through the PATEN programs, such as the procurement of facility services, the system of the services which is more modern than before and the behavior of the employees area consistent with the standard of the services.The driving sectors of the success of PATEN are the capacity of organization, coordination and interaction each actors who are involved in the program, and the strategy of information delivery through persuasive approach which improves services, such as the enhancement of the infrastructures. Furthermore, it has positive impact to the community relate to the satisfaction of the community toward the services, although there is limited budget for improving the capacity of human resources and the infrastructures. The conclusion of the research is the provision of public services through the PATEN program is related with the employees of the PATEN program, so the necessity of the bureaucratic reformation is strongly needed to achieve the good governance. Consequently, the PATEN policy can generate the institutions which have commitment for improving the bureaucratic reformation and noticing the community necessity in public services.Keywords: The bureaucratic reformation, PATEN and, public services